2019
DOI: 10.3390/f10111007
|View full text |Cite
|
Sign up to set email alerts
|

Forest Phenology Dynamics to Climate Change and Topography in a Geographic and Climate Transition Zone: The Qinling Mountains in Central China

Abstract: Forest ecosystems in an ecotone and their dynamics to climate change are growing ecological and environmental concerns. Phenology is one of the most critical biological indicators of climate change impacts on forest dynamics. In this study, we estimated and visualized the spatiotemporal patterns of forest phenology from 2001 to 2017 in the Qinling Mountains (QMs) based on the enhanced vegetation index (EVI) from MODerate-resolution Imaging Spectroradiometer (MODIS). We further analyzed this data to reveal the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(25 citation statements)
references
References 80 publications
(135 reference statements)
4
21
0
Order By: Relevance
“…It has been used to analyze and interpolate multivariate data using a smooth spline function. It can perform reasonable statistical analysis and data diagnosis on data, and can analyze the spatial distribution of data to realize spatial interpolation (Hutchinson, 1998;Xia et al, 2019).…”
Section: Climatic Datamentioning
confidence: 99%
See 2 more Smart Citations
“…It has been used to analyze and interpolate multivariate data using a smooth spline function. It can perform reasonable statistical analysis and data diagnosis on data, and can analyze the spatial distribution of data to realize spatial interpolation (Hutchinson, 1998;Xia et al, 2019).…”
Section: Climatic Datamentioning
confidence: 99%
“…Qu et al (2018) showed that temperature is a controlling factor determining the vegetation greenness in the Yangtze River Basin, and the response of vegetation to precipitation is relatively lower because of the abundant water. Xia et al (2019) suggested that the variation in vegetation responses to diurnal temperature changes is important for understanding the changes in vegetation photosynthetic activity in a warming world. Meanwhile, land use changes caused by ecological restoration project is the major driving factor for improving vegetation conditions in YRB, and the spatial distributions between human-induced GSN increasing trends and areas with increased forest have a strong consistency in the north of YRB.…”
Section: The Effects Of Climate Change On Ndvimentioning
confidence: 99%
See 1 more Smart Citation
“…Damage to the ecological environment is a major global issue that needs to be studied and resolved [ 1 , 2 ]. However, with an increase in the scope and intensity of human social and economic activities, human disturbance has produced a series of significant negative problems on different regional scales related to land cover, biodiversity, hydrological systems and local climate [ 1 , 3 , 4 ], such as ecosystem degradation, environmental pollution and global warming [ 5 , 6 , 7 ]. At the same time, the ecological environment limits human social and economic development to a certain extent, resulting in a gradual realization that the maintenance of ecosystem health is very important.…”
Section: Introductionmentioning
confidence: 99%
“…ARIATIONS in soil moisture strongly affect surface energy balances, regional runoff, land erosion and vegetation productivity [1]- [2]. Hence, the ability to detect and monitor soil moisture affects almost every aspect of society (e.g., social, economic, humanitarian and environmental segments of society).…”
Section: Introductionmentioning
confidence: 99%